Efek Konsumsi Alkohol dan Merokok Pada Wanita Hamil - Katya Rizqita Fitriana (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Active or passive use of alcohol and cigarettes can cause negative effects on the human body. Alcohol is one if a teratogenic substance than can cause an interference with pregnancy. Alcohol can criss the placenta barrier and it is know that alcohol metabolism in the fetus is twice slower than the mother. The use of cigarettes both active and passively in pregnant women can increase levels of carbon monoxide and nicotine in the blood of the mother and fetus. Increased levels of carbon monoxide will cause a decrease in oxygen levels delivered to the placenta, an increase in nicotine is know to cause distruption of brain growth that will produce cognitive, emotional, and behavioral problem in children. The effects of exposure to cigarettes anda alcohol are known to be one of the factors of spontaneous abortion, orofacial clefts, premature birth, anal atresia, low birth weight, growth retardation, placental abruption, stillbirth, and sudden infant death syndrome (SIDS).